If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 12 = 24 Reorder the terms: 12 + 3n = 24 Solving 12 + 3n = 24 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3n = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 3n = 24 + -12 3n = 24 + -12 Combine like terms: 24 + -12 = 12 3n = 12 Divide each side by '3'. n = 4 Simplifying n = 4
| 6+2(Z-3)=-5z+3 | | 11m+5n-5m+7n= | | 56=10log(x) | | 2m=16-9 | | 3c+6=33 | | 14x-3=9x-15 | | -3+6k=9 | | 62+3y=36 | | 36=2.4/(.12-x) | | 1/6-1/3=2/3 | | -4t-7(2t-5)-11=-12 | | 2x+6y-20=0 | | (2x)(x+10)+110=360 | | 5(2x+3)+-3(2+x)=22 | | 2x^2+2y^2-10x-18y=0 | | 10x+-18x=4x-6 | | N-8-7+13=1+4n | | 10x-18x=4-6 | | 5x+9y-4x-4y= | | 300x^14+260x^12+20=0 | | X^2+29x=-54 | | 5(n+4)+24=-2n-8 | | 12/18=n36 | | 11r-6t=45 | | 3x+4(x+1)=2(x+7) | | 3(3x+4)+2(5x-3)= | | 6+2(z-3)=5z+3 | | 12-3x=x-4(2+2x) | | 9(3x+2)+4(x-4)=33 | | 5c-1=39 | | 4(x-1)-x= | | 4(x-1)+x= |